Peru at the brink of economic collapse: Current problems and policy options - Uwe Corsepius (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
Since 1988 Peru has plunged into a deep economic crisis which has already caused severe social strife and threatens to uproot the young democratic system. The present government seems to be unable to arrest the precipitous decline of per capita income of the Peruvian population. Therefore, the result of the next presidential elections in early 1990 will hinge on the credibility of the candidates' economic reform programmes. The Peruvian economy is suffering from large government deficits, a declining international competitiveness, an outdated and underutilised capital stock, and substantial arrears on the high debt burden. These structural deficiencies have resulted in an economic quandary which is characterized by hyperinflation, a drain of foreign exchange reserves, a dramatic decline of output, and mass unemployment. The economic plight of Peru can largely be attributed to a long history of policy failures. Adverse external developments such as low commodity prices or high interest rates were of minor importance. A comprehensive and consistent policy reform programme accompanied by foreign financial support would go a long way in bringing Peru back to a sustained and socially acceptable growth path. Priority areas for policy reform are to stop hyperinflation by public expenditure cuts and a tax reform, to improve domestic resource mobilisation by dismantling financial sector regulations, and to regain international competitiveness by exchange rate adjustment and lower import protection. Successful adjustment of the Peruvian economy will require an internationally-agreed temporary suspension of debt service payments and a supply of fresh funds to finance restructuring. Domestically, social hardship caused by adjustment has to be eased by targeted food subsidies to the poor.
Keywords: 330; Konjunktur; Strukturpolitik; Hyperinflation; Wirtschaftspolitik; Peru